The dematerialisation of Karl Marx : literature and marxist theory - Jackson, Leonard (Longman, 1994)
This volume constitutes both an attack on modern left wing literary theory - the main product of the last Marxist renaissance in the past thirty years - and a defence of the one element of Marxism which, in the general collapse, modern theorists have been happiest to lose, its economic materialism. It traces Marxist theory from its beginnings in Hegelian idealism to its end in Althusser's structuralism, and concludes that while Marxist economics will not work, and the type of revolution prophesied was fantasy, the principle of historical materialism remains intact and defensible. This will be a key text in literary and cultural studies as well as being of interest to students on philosophy and sociology courses.